The Island Called Paradise : Cuba in History, Literature, and the Arts - Beidler, Philip D. (Book collections on Project MUSE., 2014)
A personal and cultural mediation, Philip D. Beidler's The Island Called Paradise explores the fascinating ways Cuban history and culture have permeated North American consciousness, and vice versa. In The Island Called Paradise, Philip D. Beidler shares his personal discovery of the vast, rich, and astonishing history of the island of Cuba and the interrelatedness of Cuba and the US. Cuba first entered Beidler's consciousness in the early 1960s when he watched with mesmerized anxiety the televised reports of the Cuban missile crisis, a conflict that reduced a multifaceted, centuries-old history.